Sandwich-structure MCMB-Si-C silicon-carbon negative electrode material and preparation method and application thereof
By adopting the preparation method of the sandwich structure MCMB@Si@C silicon carbon negative electrode material, the existing process complexity and poor bonding force are solved, the stability and performance of the material are improved, and it is suitable for industrial production applications.
Patent Information
- Application Number
- CN202411681443.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing MCMB-Si silicon carbon anode material has complex preparation processes and poor binding force, resulting in poor stability in the charge and discharge process, poor rate performance and cycle performance.
The preparation method of the sandwich structure MCMB@Si@C silicon carbon negative electrode material is adopted. The nano-silicon is uniformly adhered to the surface of the meso-phase carbon microspheres through thermal polymerization, and the sandwich structure is formed by the liquid carbon layer covering it to simplify the process and improve the bonding force of the material.
The process is simplified, and the cycle stability and rate performance of the material are improved, which alleviates the volume changes during lithium embedding/delithation and improves the overall performance of the battery.
Smart Images

Figure CN119560509A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a silicon-carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of new energy vehicles and various electronic products, the application requirements for lithium-ion battery performance are getting higher and higher. Among them, lithium-ion battery anode materials, as an important component of lithium-ion batteries, have always been the focus of researchers. Silicon-carbon anode materials have become the focus of research because they combine the advantages of traditional carbon anode materials and silicon-based anode materials, and can effectively improve the energy density of anode materials, improve cycle performance and rate performance.
[0003] Among the numerous carbon negative electrode materials, mesophase carbon microspheres (MCMB) are beneficial to the insertion and extraction of lithium ions in different directions due to their spherical shape and unique lamellar structure, and their volume changes little during the charge and discharge process. However, compared with artificial graphite and natural graphite, the capacity of mesophase carbon microspheres is relatively low, and the surface density and graphitization degree of mesophase carbon microspheres prepared by traditional processes are high under high-temperature heat treatment, which is not conducive to rapid lithium insertion and extraction reactions, affecting the rate performance and high and low temperature performance of negative electrode materials. Silicon-based negative electrode materials have higher specific capacity and can effectively improve the energy density of batteries, but they have large volume changes and poor cycle performance during charge and discharge. Based on the above problems, researchers proposed to prepare MCMB-Si composite materials by combining the above two materials, and give full play to the synergistic effect between the two materials through reasonable structural design. The current research results have confirmed the feasibility of this method.
[0004] However, the current MCMB-Si silicon-carbon negative electrode materials still have some problems: First, the material preparation process is complicated. Second, the bonding force between MCMB and silicon-based materials is poor, and the stability of the charge and discharge process is poor. To solve this problem, the Chinese patent CN117525357 A proposes a silicon-carbon negative electrode material for lithium-ion batteries and its preparation method. The method adopts a multilayer silicon-carbon composite material constructed by spraying-bonding-peeling-stacking technology to achieve the overall optimization of electrochemical performance, solve the problem of a significant decrease in specific capacity of silicon-carbon composite materials as the number of cycles increases, greatly alleviate the volume change of silicon during the cycle, and maintain the integrity of the electrode. The Chinese patent CN 113193183 A proposes a method for preparing a silicon-carbon composite material with a double carbon layer structure. The invention uses loose and porous pyrolytic carbon as the middle layer carbon to coat nanosilicon, and dense pyrolytic carbon as the outer layer carbon to form a double carbon layer coated nanosilicon structure. This structure effectively improves the volume change during the charge and discharge process, giving the material high specific capacity, high first coulomb efficiency and long cycle life. However, the middle carbon layer is easily destroyed during the processing of the electrode, which makes the conductive performance of the material worse. In addition, the invention uses a hot compaction process to improve the contact tightness between the silicon and carbon phases, and the interaction force between the two phases is still weak. The Chinese patent CN109659514 A proposes a silicon-carbon negative electrode material based on mesophase carbon microspheres and a preparation method thereof. The invention uses mesophase carbon microspheres as the core, and the outermost layer is coated with an amorphous carbon layer. Combined with the hydrolysis of ethyl orthosilicate and the magnesium thermal reduction method, a silicon-carbon negative electrode material with nano-silicon uniformly wrapped in mesophase carbon microspheres is prepared. The material has excellent lithium storage characteristics when used as a lithium battery negative electrode material. However, the material preparation process of the invention is too complicated to achieve industrial production and application.
[0005] Therefore, how to simplify the process of preparing silicon-carbon negative electrode materials from MCMB and silicon-based materials, facilitate industrial production applications, alleviate volume changes during lithium insertion / delithiation, and improve the conductivity, cycle performance and rate performance of silicon-carbon negative electrode materials is an industry problem that needs to be solved urgently. Summary of the invention
[0006] Based on this, the present invention proposes a sandwich structure MCMB@Si@C silicon-carbon negative electrode material and its preparation method and application. The preparation method has the characteristics of simple process and easy industrial production. The obtained silicon-carbon negative electrode material can effectively alleviate the volume change during the lithium insertion / de-lithiation process and improve its cycle stability and rate performance.
[0007] In order to achieve the above object, the technical solution of the present invention is achieved as follows: A method for preparing a sandwich structure MCMB@Si@C silicon-carbon negative electrode material, the steps are as follows: (1) mixing asphalt and nano-silicon and performing a thermal polymerization reaction to obtain a thermal polymerization product containing mesophase carbon microspheres loaded with nano-silicon; (2) the thermal polymerization product obtained in step (1) is dissolved by stirring and heating with organic oil and filtered, and the filter cake is repeatedly extracted with an organic solvent as a reflux liquid, and the insoluble matter is dried to obtain mesophase carbon microspheres loaded with nano-silicon on the surface, i.e., MCMB@Si material; (3) The raw materials of MCMB@Si material and coated carbon material are mixed and subjected to liquid phase carbon layer coating treatment; after high-temperature carbonization in an inert atmosphere, a sandwich structured MCMB@Si@C silicon-carbon negative electrode material is obtained.
[0008] Preferably, the asphalt in step (1) is at least one of petroleum asphalt, coal asphalt, modified coal asphalt, coal tar and secondary petroleum heavy oil; the nano silicon is at least one of elemental silicon, silicon dioxide and silicon monoxide, with a particle size of 50-200 nm; the mass ratio of the asphalt to the nano silicon is 100:1-10.
[0009] Preferably, the protective atmosphere in the thermal polymerization reaction in step (1) is nitrogen and / or argon, the thermal polymerization reaction pressure is 0.1-2 MPa, the reaction temperature is 350-450° C., the reaction time is 3-6 h, and the stirring rate is 100-300 rpm.
[0010] Preferably, in step (2), the mass ratio of the organic oil to the thermal polymerization product is 3-5:1, the temperature for heating and dissolving is 80-120° C., the stirring rate during dissolution is 100-300 rpm, and the stirring time is 0.5-3 h.
[0011] Preferably, in step (2), the organic oil is washing oil or gasoline; the organic solvent is quinoline and ethanol or tetrahydrofuran; the drying temperature is 60-80°C, and the drying time is 6-24 h.
[0012] Preferably, the liquid phase carbon layer coating process type in step (3) is liquid phase physical coating or liquid phase in-situ chemical coating.
[0013] Preferably, the coated carbon material in step (3) is one or more of asphalt, coated asphalt, phenolic resin, organic polymers such as polydopamine, graphite, and amorphous carbon, and the mass ratio of the coated carbon material to the MCMB@Si material is 30-100:100.
[0014] Preferably, the high temperature carbonization treatment temperature in step (3) is 800-1400°C, the heating rate is 3-10°C / min, and the temperature is kept constant for 0.5-3h; the protective atmosphere is nitrogen and / or argon, and the gas flow rate is 30-100 mL min -1 .
[0015] Preferably, the sandwich structure MCMB@Si@C silicon-carbon negative electrode material prepared by the method has a core of mesophase carbon microspheres, a middle layer of nano-silicon, and an outermost layer of a dense carbon layer.
[0016] Preferably, the sandwich structure MCMB@Si@C silicon-carbon negative electrode material is used in lithium-ion batteries.
[0017] The present invention has the following beneficial effects: (1) The present invention adopts a thermal polymerization reaction process. During the growth of the mesophase carbon microspheres, there is a certain solid-liquid interface driving force. This driving force will cause the silicon particles in the system to move to the surface of the mesophase carbon microspheres, and then evenly adhere to the surface of the mesophase carbon microspheres, completing the self-assembly between the mesophase carbon microspheres and the silicon particles in one step; further, the preparation of the sandwich structure MCMB@Si@C silicon-carbon negative electrode material is realized through liquid phase coating.
[0018] (2) The silicon-carbon negative electrode material with a sandwich structure of the present invention is composed of mesophase carbon microspheres, nano-silicon and dense carbon layers from the inside to the outside. The core mesophase carbon microspheres have a strong lithium storage capacity, and their large specific surface area gives the nano-silicon a good dispersion effect. The outermost dense carbon layer can play a dual role as a buffer layer and a conductive layer. These factors work together to give the sandwich structured silicon-carbon negative electrode material excellent cycle stability and rate performance, which can effectively improve the volume change phenomenon during the lithium removal / lithium insertion process, and is conducive to the formation of a more stable solid electrolyte membrane.
[0019] (3) The process for preparing MCMB@Si@C silicon-carbon negative electrode material according to the present invention is simple, highly operable and easy to realize industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 Figure 1 is the SEM image of the MCMB@Si material of Example 1 of the present invention, and Figures a and b are SEM images at different magnifications.
[0022] Figure 2 The SEM image of the sandwich structure MCMB@Si@C silicon-carbon negative electrode material with the outermost layer coated with phenolic resin in Example 1 of the present invention (as shown in FIG. Figure 2 Figure (a)) and EDS diagram (as shown Figure 2 (b), (c), (d)), where Figure 2 (b) is the EDS diagram of silicon and carbon. Figure 2 (c) is the EDS image of carbon element in MCMB@Si@C silicon-carbon negative electrode material. Figure 2 (d) is the EDS image of silicon element in MCMB@Si@C silicon-carbon negative electrode material. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The asphalt, nano-silicon and other raw materials used in the present invention are all commercially available products; the asphalt, coated asphalt, phenolic resin, polydopamine, graphite and amorphous carbon used are all commercially available products or homemade in the laboratory.
[0025] Example 1 A method for preparing a sandwich structure MCMB@Si@C silicon-carbon negative electrode material, the steps are as follows: 70g of natural petroleum asphalt was weighed, crushed and mixed with 1g of nano-silicon, which was elemental silicon with a particle size of 150nm, and placed together in a high-temperature and high-pressure reactor. After sealing, high-purity nitrogen was introduced to replace the air in the reactor, and then nitrogen was injected into the reactor and the system pressure was maintained at 1.0 MPa. The temperature was raised to 410℃ at a certain heating rate, and the insulation time was 4 h, and the stirring rate was 200 rpm. After the reaction was completed, it was naturally cooled to about 200℃, and the pressure was released and the reactor was opened to allow the asphalt to flow out in a molten state to obtain a thermal polymerization product containing MCMB@Si material. The above-mentioned thermal polymerization product and washing oil were mixed in a mass ratio of 1: 3, heated to 80℃, stirred for 2 h, and stirred at a rate of 100rpm. The above-mentioned mixed solution was filtered and collected while hot, and the obtained filter cake was crushed and placed in a cellulose filter paper cylinder. The filter paper cylinder was then placed in a Soxhlet extractor and repeatedly rinsed with quinoline as the reflux liquid until the reflux liquid was colorless. Then, anhydrous ethanol was used as the reflux liquid for extraction. The obtained material was vacuum dried at 80℃ for 24 h, and the obtained brown powder was MCMB@Si material.
[0026] Figure 1 This is the SEM image of the MCMB@Si material in this embodiment; it can be seen from the figure that the nano-silicon is successfully loaded and dispersed on the surface of the mesophase carbon microspheres, forming a silicon-carbon material with the mesophase carbon microspheres as the core; the particle size of the MCMB@Si microspheres is 5-15μm.
[0027] Weigh 10 g of the MCMB@Si material obtained above and 0.6 g of hexadecyltrimethylammonium bromide and mix them in 200 mL of deionized water. Ultrasonicate for 30 min to mix evenly. Then, under the premise of heating and stirring in a 40 °C water bath, add 2 g of resorcinol, mL of formaldehyde and 15 mL of ammonia water in sequence and react for 6 h. Then stop stirring and age overnight. Centrifuge the above solution and wash the product with water and ethanol several times. The product is heated at 5 °C min -1 The temperature was raised to 800 °C and carbonized for 3 h to obtain MCMB@Si@C-RF silicon-carbon negative electrode material.
[0028] Figure 2 (a) is a SEM image of the sandwich structure MCMB@Si@C silicon-carbon anode material with the outermost layer coated with phenolic resin in this embodiment. It can be seen from the figure that after being coated with phenolic resin, the surface of the obtained silicon-carbon anode material is smooth and free of small balls. EDS scanning ( Figure 2 In (b), (c), and (d), it is confirmed that the outermost layer is a dense carbon layer formed after coating with phenolic resin.
[0029] Lithium battery assembly and performance An appropriate amount of sandwich structure MCMB@Si@C-RF silicon-carbon negative electrode material, polyvinylidene fluoride and acetylene black, and an appropriate amount of N-methylpyrrolidone were weighed in a mass ratio of 8:1:1, and evenly coated on copper foil after ball milling at a rate of 150 rpm for 2 h. The battery pole piece was obtained after vacuum drying at 80 °C for 12 h. The obtained battery pole piece was used as the working electrode and the lithium sheet as the counter electrode to assemble the lithium-ion button cell in the glove box. At a current density of 200 mA g -1 Under the condition of first discharge capacity of 707.2 mA hg -1 The first coulombic efficiency is 83%, and the capacity retention rate after 1000 cycles is 85%. -1 , 0.2 A g -1 , 0.4 A g -1 , 0.8 A g -1 and 1.6 A g -1 At a current density of 803 mAh g -1 、681 mAh g -1 、593 mAh g -1 , 536 mAh g -1 , 487 mAh g -1 , 435mAh g -1 The reversible capacity of the battery recovered to 654 mAh g -1 . It has excellent rate performance and cycle stability.
[0030] Example 2 A method for preparing a sandwich structure MCMB@Si@C silicon-carbon negative electrode material, the steps are as follows: 70g of natural petroleum asphalt was weighed, crushed and mixed with 1g of nano-silicon, which was elemental silicon with a particle size of 150nm, and placed together in a high-temperature and high-pressure reactor. After sealing, high-purity nitrogen was introduced to replace the air in the reactor, and then nitrogen was injected into the reactor and the system pressure was maintained at 1.0 MPa. The temperature was raised to 410℃ at a certain heating rate, and the insulation time was 4 h, and the stirring rate was 200 rpm. After the reaction was completed, it was naturally cooled to about 200℃, and the pressure was released and the reactor was opened to allow the asphalt to flow out in a molten state to obtain a thermal polymerization product containing MCMB@Si material. The above-mentioned thermal polymerization product and washing oil were mixed in a mass ratio of 1: 3, heated to 80℃, stirred for 2 h, and stirred at a rate of 100rpm. While hot, the above-mentioned mixed solution was filtered and the filter cake obtained by suction filtration was collected. The filter cake was crushed and placed in a cellulose filter paper cylinder. The filter paper cylinder was then placed in a Soxhlet extractor and repeatedly rinsed with quinoline as the reflux liquid until the reflux liquid was colorless. Then, anhydrous ethanol was used as the reflux liquid for extraction. The obtained material was vacuum dried at 80℃ for 24 h, and the obtained brown powder was MCMB@Si material.
[0031] Weigh 10 g of the MCMB@Si material obtained above and disperse it in 75 mL of 10 mmol L -1 After uniformly mixing with Tris-HCl buffer solution (pH = 8.5), 5 g of dopamine hydrochloride was added and the reaction was stirred at room temperature overnight. Centrifugation was performed, and the mixture was washed several times with deionized water and dried under vacuum at 80 °C for 12 h to obtain a carbon precursor. The above materials were placed in a tube furnace and heated at 5 °C min under an argon atmosphere. -1 The temperature was raised to 800 °C and carbonized for 3 h to obtain the sandwich structure MCMB@Si@C-PDA silicon-carbon negative electrode material.
[0032] Lithium battery assembly and performance Appropriate amounts of sandwich structure MCMB@Si@C-PDA silicon-carbon negative electrode material, polyvinylidene fluoride and acetylene black, and appropriate amounts of N-methylpyrrolidone were weighed in a mass ratio of 8:1:1, and evenly coated on copper foil after ball milling at a rate of 150 rpm for 2 h. The battery pole piece was obtained after vacuum drying at 80 °C for 12 h. The obtained battery pole piece was used as the working electrode and the lithium sheet as the counter electrode to assemble the lithium-ion button cell in the glove box. At a current density of 200 mA g -1 The first reversible specific capacity is 914 mA h g -1 The first coulombic efficiency was 65%, and the capacity retention rate after 1000 cycles was 71%. -1, 0.2 A g -1 , 0.4 A g -1 , 0.8 A g -1 and 1.6 A g -1 At a current density of 895 mAh g -1 , 591 mAh g -1 , 523 mAh g -1 , 486 mAh g -1 , 407 mAh g -1 , 355mAh g -1 The reversible capacity of the battery is 594 mAh g-1, and when the current density is restored, the reversible capacity is restored to 594 mAh g-1. It has good rate performance and cycle stability.
[0033] Example 3 A method for preparing a sandwich structure MCMB@Si@C silicon-carbon negative electrode material, the steps are as follows: 70g of natural petroleum asphalt was weighed, crushed and mixed with 1g of nano-silicon, which was elemental silicon with a particle size of 150nm, and placed together in a high-temperature and high-pressure reactor. After sealing, high-purity nitrogen was introduced to replace the air in the reactor, and then nitrogen was injected into the reactor and the system pressure was maintained at 1.0 MPa. The temperature was raised to 410℃ at a certain heating rate, and the insulation time was 4 h, and the stirring rate was 200 rpm. After the reaction was completed, it was naturally cooled to about 200℃, and the pressure was released and the reactor was opened to allow the asphalt to flow out in a molten state to obtain a thermal polymerization product containing MCMB@Si material. The above-mentioned thermal polymerization product and washing oil were mixed in a mass ratio of 1: 3, heated to 80℃, stirred for 2 h, and stirred at a rate of 100rpm. While hot, the above-mentioned mixed solution was filtered and the filter cake obtained by suction filtration was collected. The filter cake was crushed and placed in a cellulose filter paper cylinder. The filter paper cylinder was then placed in a Soxhlet extractor and repeatedly rinsed with quinoline as the reflux liquid until the reflux liquid was colorless. Then, anhydrous ethanol was used as the reflux liquid for extraction. The obtained material was vacuum dried at 80℃ for 24 h, and the obtained brown powder was MCMB@Si material.
[0034] Weigh 10g of the MCMB@Si material obtained above and mix it with 5g of coated asphalt, disperse it in tetrahydrofuran solution, heat it to 40°C, stir it at 100rpm, until the tetrahydrofuran solvent is completely evaporated. Then transfer it to a tube furnace and heat it under argon atmosphere at a gas flow rate of 30 mL min -1 , at 5℃ min -1 The temperature was raised to 800 °C and carbonized for 3 h to obtain the sandwich structure MCMB@Si@C-CP silicon-carbon negative electrode material.
[0035] Lithium battery assembly and performance Weigh appropriate amounts of sandwich structure MCMB@Si@C-CP silicon-carbon negative electrode materials, polyvinylidene fluoride and acetylene black, and appropriate amounts of N-methylpyrrolidone in a mass ratio of 8:1:1, ball mill at a rate of 150 rpm for 2 h, and evenly coat copper foil. After vacuum drying at 80 °C for 12 h, the battery pole piece was obtained. The obtained battery pole piece was used as the working electrode and the lithium sheet as the counter electrode to assemble the lithium-ion button cell in the glove box. At a current density of 200 mA g -1 The first reversible specific capacity is 732 mA hg -1 The first coulombic efficiency is 80%, and the capacity retention rate after 1000 cycles is 83%. -1 , 0.2 A g -1 , 0.4 A g -1 , 0.8 A g -1 and 1.6 A g -1 At a current density of 643 mAh g -1 , 501 mAh g -1 、473 mAh g -1 , 420 mAh g -1 、362 mAh g -1 , 299 mAh g -1 The reversible capacity of the battery recovered to 483 mAh g -1 . It has excellent rate performance and cycle stability.
[0036] Example 4 A method for preparing a sandwich structure MCMB@Si@C silicon-carbon negative electrode material, the steps are as follows: 70g of natural petroleum asphalt was weighed, crushed and mixed with 1g of nano-silicon, which was elemental silicon with a particle size of 150nm, and placed together in a high-temperature and high-pressure reactor. After sealing, high-purity nitrogen was introduced to replace the air in the reactor, and then nitrogen was injected into the reactor and the system pressure was maintained at 2.0 MPa. The temperature was raised to 350℃ at a certain heating rate, and the insulation time was 6 h, and the stirring rate was 100 rpm. After the reaction was completed, it was naturally cooled to about 200℃, and the pressure was released and the reactor was opened to allow the asphalt to flow out in a molten state to obtain a thermal polymerization product containing MCMB@Si material. The above-mentioned thermal polymerization product and gasoline were mixed in a mass ratio of 1: 4, heated to 100℃, stirred for 1 h, and stirred at a rate of 100rpm. The above-mentioned mixed solution was filtered and collected while hot, and the obtained filter cake was crushed and placed in a cellulose filter paper cylinder. The filter paper cylinder was then placed in a Soxhlet extractor and repeatedly rinsed with quinoline as the reflux liquid until the reflux liquid was colorless. Then, anhydrous ethanol was used as the reflux liquid for extraction. The obtained material was vacuum dried at 60°C for 18 h, and the obtained brown powder was MCMB@Si material.
[0037] 10 g of the MCMB@Si material obtained above and 3 g of graphite were weighed and dispersed in 200 mL of ethanol. Then, the mixture was heated and stirred at 40 °C with a stirring rate of 100 rpm until the ethanol solvent was completely evaporated. Then, the mixture was transferred to a tube furnace and heated under an argon atmosphere with a gas flow rate of 80 mL min -1 The product was heated at 3 °C min -1 The temperature was raised to 800 °C and carbonized for 3 h to obtain MCMB@Si@C-graphite silicon-carbon negative electrode material.
[0038] Lithium battery assembly and performance The sandwich structure MCMB@Si@C-graphite silicon-carbon negative electrode material, polyvinylidene fluoride and acetylene black, and an appropriate amount of N-methylpyrrolidone were weighed in a mass ratio of 8:1:1, and evenly coated on copper foil after ball milling at a rate of 150 rpm for 2 h. The battery pole piece was obtained after vacuum drying at 80 ° C for 12 h. The obtained battery pole piece was used as the working electrode and the lithium sheet as the counter electrode to assemble the lithium-ion button cell in the glove box. At a current density of 200 mA g -1 The first reversible specific capacity is 680mA hg -1 The first coulombic efficiency is 80%, the capacity retention rate after 1000 cycles is 78%, and the -1 , 0.2 A g -1 , 0.4 A g -1 , 0.8 A g -1 and 1.6 A g -1 At a current density of 565 mAh g -1 , 434 mAh g -1 , 411 mAh g -1 , 355mAh g -1 , 302 mAh g -1 , 255mAh g -1 The reversible capacity of the battery recovered to 435 mAh g -1 . It has excellent rate performance and cycle stability.
[0039] Example 5 A method for preparing a sandwich structure MCMB@Si@C silicon-carbon negative electrode material, the steps are as follows: 70g of natural petroleum asphalt was weighed, crushed and mixed with 10g of nano-silicon, which was elemental silicon with a particle size of 150nm, and placed together in a high-temperature and high-pressure reactor. After sealing, high-purity nitrogen was introduced to replace the air in the reactor, and then nitrogen was injected into the reactor and the system pressure was maintained at 0.1MPa. The temperature was raised to 450℃ at a certain heating rate, and the insulation time was 3 h, and the stirring rate was 300 rpm. After the reaction was completed, it was naturally cooled to about 200℃, and the pressure was released and the reactor was opened to allow the asphalt to flow out in a molten state to obtain a thermal polymerization product containing MCMB@Si material. The above thermal polymerization product and gasoline were mixed in a mass ratio of 1:3, heated to 120℃, stirred for 0.5 h, and stirred at a rate of 200rpm. While hot, the above mixture was filtered and collected by suction filtration, and the obtained filter cake was crushed and placed in a cellulose filter paper cylinder. The filter paper cylinder was then placed in a Soxhlet extractor and repeatedly rinsed with quinoline as the reflux liquid until the reflux liquid was colorless. Then, anhydrous ethanol was used as the reflux liquid for extraction. The obtained material was vacuum dried at 70°C for 10 hours, and the obtained brown powder was MCMB@Si material.
[0040] Weigh 10 g of the MCMB@Si material obtained above and 10 g of the coated asphalt, stir and disperse them in tetrahydrofuran, heat to 40 °C and stir at a stirring rate of 100 rpm until the tetrahydrofuran solvent is completely evaporated. Then transfer it to a tube furnace and heat it in an argon atmosphere at a gas flow rate of 100 mL min -1 The product was heated at 10°C min -1 The temperature was raised to 1400°C for 1.5 h to obtain the MCMB@Si@C-coated asphalt silicon-carbon negative electrode material.
[0041] Lithium battery assembly and performance The above sandwich structure MCMB@Si@C-CP silicon-carbon negative electrode material, polyvinylidene fluoride and acetylene black, and an appropriate amount of N-methylpyrrolidone were weighed in a mass ratio of 8:1:1, and evenly coated on copper foil after ball milling at a rate of 150 rpm for 2 h. The battery pole piece was obtained after vacuum drying at 80 ° C for 12 h. The obtained battery pole piece was used as the working electrode and the lithium sheet as the counter electrode to assemble the lithium-ion button cell in the glove box. At a current density of 200 mA g -1 The first reversible specific capacity is 852mA hg -1 The first coulombic efficiency was 89%, and the capacity retention rate after 1000 cycles was 88%. -1 , 0.2 A g -1 , 0.4 A g -1 , 0.8 A g -1 and 1.6 A g -1 At a current density of 796 mAh g -1 、651 mAh g-1 , 615mAh g -1 , 572 mAh g -1 , 511mAh g -1 , 445mAh g -1 The reversible capacity of the battery recovered to 714 mAh g -1 . It has excellent rate performance and cycle stability.
[0042] Example 6 A sandwich structure MCMB@Si@C silicon-carbon negative electrode material and a preparation method, the steps are as follows: 70g of natural petroleum asphalt was weighed, crushed and mixed with 1g of nano-silicon, which was silicon dioxide with a particle size of 150nm, and placed together in a high-temperature and high-pressure reactor. After sealing, high-purity nitrogen was introduced to replace the air in the reactor, and then nitrogen was injected into the reactor and the system pressure was maintained at 1.0 MPa. The temperature was raised to 410℃ at a certain heating rate, and the insulation time was 4 h, and the stirring rate was 200 rpm. After the reaction was completed, it was naturally cooled to about 200℃, and the pressure was released and the reactor was opened to allow the asphalt to flow out in a molten state to obtain a thermal polymerization product containing MCMB@Si material. The above-mentioned thermal polymerization product and washing oil were mixed in a mass ratio of 1: 3, heated to 80℃, stirred for 2 h, and stirred at a rate of 100rpm. The above-mentioned mixed solution was filtered and collected while hot, and the obtained filter cake was crushed and placed in a cellulose filter paper cylinder. The filter paper cylinder was then placed in a Soxhlet extractor and repeatedly rinsed with quinoline as the reflux liquid until the reflux liquid was colorless. Then, tetrahydrofuran was used as the reflux liquid for extraction. The obtained material was dried under vacuum at 80°C for 6 hours, and the obtained brown powder was MCMB@Si material.
[0043] 10 g of the MCMB@Si material obtained above was weighed and mixed with 6 g of coated asphalt, and dispersed in tetrahydrofuran solution, heated to 40 °C, and stirred at a rate of 100 rpm until the tetrahydrofuran solvent was completely evaporated. Then it was transferred to a tube furnace and heated under an argon atmosphere at a gas flow rate of 50 mL min -1 The product was heated at 5°C min -1 The temperature was raised to 1000℃ and carbonized for 2 h to obtain MCMB@Si@C-amorphous carbon silicon carbon negative electrode material.
[0044] Lithium battery assembly and performance The above sandwich structure MCMB@Si@C-CP silicon-carbon negative electrode material, polyvinylidene fluoride and acetylene black, and an appropriate amount of N-methylpyrrolidone were weighed in a mass ratio of 8:1:1, and evenly coated on copper foil after ball milling at a rate of 150 rpm for 2 h. The battery pole piece was obtained after vacuum drying at 80 ° C for 12 h. The obtained battery pole piece was used as the working electrode and the lithium sheet as the counter electrode to assemble the lithium-ion button cell in the glove box. At a current density of 200 mA g -1 The first reversible specific capacity is 760mA hg -1 The first coulombic efficiency was 84%, and the capacity retention rate after 1000 cycles was 82%. -1 , 0.2 A g -1 , 0.4 A g -1 , 0.8 A g -1 and 1.6 A g -1 At a current density of 665 mAh g -1 , 523 mAh g -1 , 488mAh g -1 , 432 mAh g -1 , 392mAh g -1 , 326mAh g -1 The reversible capacity is restored to 515 mAh g-1 when the current density is restored. It has excellent rate performance and cycle stability.
[0045] Comparative Example 1 This comparative example provides a MCMB@Si material and a preparation method. The difference from Example 1 is that the surface of the MCMB@Si composite material is not subjected to carbon coating treatment. The steps are as follows: Weigh 70g of natural petroleum asphalt, crush it and mix it with 1g of nano-silicon, and put it into a high-temperature and high-pressure reactor. After sealing, high-purity nitrogen is introduced to replace the air in the reactor, and then nitrogen is injected into the reactor to maintain the system pressure at 1.0 MPa. The temperature is raised to 410℃ at a certain heating rate, and the insulation time is 4 h. The stirring rate is 200 rpm. After the reaction is completed, it is naturally cooled to about 200℃, and the pressure is released and the reactor is opened to allow the asphalt to flow out in a molten state to obtain a thermal polymerization product containing MCMB@Si material. The above-mentioned thermal polymerization product and washing oil are mixed in a mass ratio of 1: 3, heated to 80℃, stirred for 2 h, and the stirring rate is 100rpm. While hot, the above-mentioned mixed solution is filtered and the filter cake obtained by suction filtration is collected. The filter cake is crushed and placed in a cellulose filter paper cylinder. The filter paper cylinder is then placed in a Soxhlet extractor and repeatedly rinsed with quinoline as the reflux liquid until the reflux liquid is colorless. Then, anhydrous ethanol is used as the reflux liquid for extraction. The obtained material was vacuum dried at 80°C for 24 h, and the obtained brown powder was MCMB@Si material.
[0046] Lithium battery assembly and performance An appropriate amount of sandwich structure MCMB@Si silicon-carbon negative electrode material, polyvinylidene fluoride and acetylene black, and an appropriate amount of N-methylpyrrolidone were weighed in a mass ratio of 8:1:1, and evenly coated on copper foil after ball milling at a rate of 150 rpm for 2 h. The battery pole piece was obtained after vacuum drying at 80 °C for 12 h. The obtained battery pole piece was used as the working electrode and the lithium sheet as the counter electrode to assemble the lithium-ion button cell in the glove box. At a current density of 200 mA g -1 The first reversible specific capacity is 663.8 mA hg -1 The first coulombic efficiency was 79%, the capacity retention rate after 1000 cycles was 65%, and the capacity retention rate after 1000 cycles was 85%. -1 , 0.2 A g -1 , 0.4 A g -1 , 0.8 Ag -1 and 1.6 A g -1 At a current density of 625 mAh g -1 、413 mAh g -1 , 265 mAh g -1 , 223 mAh g -1 , 201 mAh g -1 , 187mAh g -1 The reversible capacity of the battery recovered to 310 mAh g -1 . The rate performance and cycle stability are good.
[0047] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a sandwich structure MCMB@Si@C silicon-carbon negative electrode material, characterized in that: Here are the steps: (1) mixing asphalt and nano-silicon and performing a thermal polymerization reaction to obtain a thermal polymerization product containing mesophase carbon microspheres loaded with nano-silicon; (2) the thermal polymerization product obtained in step (1) is dissolved by stirring and heating with organic oil and filtered, and the filter cake is repeatedly extracted with an organic solvent as a reflux liquid, and the insoluble matter is dried to obtain mesophase carbon microspheres loaded with nano-silicon on the surface, i.e., MCMB@Si material; (3) The raw materials of MCMB@Si material and coated carbon material are mixed and subjected to liquid phase carbon layer coating treatment; after high-temperature carbonization in an inert atmosphere, a sandwich structured MCMB@Si@C silicon-carbon negative electrode material is obtained.
2. The method for preparing the sandwich structure MCMB@Si@C silicon-carbon negative electrode material according to claim 1, characterized in that: The asphalt in step (1) is at least one of petroleum asphalt, coal asphalt, modified coal asphalt, coal tar and secondary petroleum heavy oil; the nano silicon is at least one of elemental silicon, silicon dioxide and silicon monoxide, with a particle size of 50-200 nm; the mass ratio of the asphalt to the nano silicon is 100: 1-10.
3. The method for preparing the sandwich structure MCMB@Si@C silicon-carbon negative electrode material according to claim 1, characterized in that: In the thermal polymerization reaction in step (1), the protective atmosphere is nitrogen and / or argon, the thermal polymerization reaction pressure is 0.1-2 MPa, the reaction temperature is 350-450° C., the reaction time is 3-6 h, and the stirring rate is 100-300 rpm.
4. The method for preparing the sandwich structure MCMB@Si@C silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (2), the organic oil is washing oil or gasoline; the organic solvent is quinoline and ethanol or tetrahydrofuran; the mass ratio of the organic oil to the thermal polymerization product is 3-5:1, the heating and dissolving temperature is 80-120°C, and the dissolving time is 0.5-3h.
5. The method for preparing the sandwich structure MCMB@Si@C silicon-carbon negative electrode material according to claim 1, characterized in that: The drying temperature in step (2) is 60-80° C. and the drying time is 6-24 hours.
6. The method for preparing the sandwich structure MCMB@Si@C silicon-carbon negative electrode material according to claim 1, characterized in that: The liquid phase carbon layer coating process type in step (3) is liquid phase physical coating or liquid phase in-situ chemical coating.
7. The method for preparing the sandwich structure MCMB@Si@C silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (3), the coated carbon material is one or more of asphalt, coated asphalt, phenolic resin, polydopamine, graphite and amorphous carbon, and the mass ratio of the coated carbon material to the MCMB@Si material is 3-10:
10.
8. The method for preparing the sandwich structure MCMB@Si@C silicon-carbon negative electrode material according to claim 1, characterized in that: In the step (3), the high temperature carbonization treatment temperature is 800-1400°C, the heating rate is 3-10°C / min, and the temperature is maintained for 0.5-3h; the inert atmosphere is nitrogen and / or argon.
9. The sandwich structure MCMB@Si@C silicon-carbon negative electrode material prepared by the method according to any one of claims 1 to 8, characterized in that: The core of the sandwich structure MCMB@Si@C silicon-carbon negative electrode material is mesophase carbon microspheres, the middle layer is nano-silicon, and the outermost layer is a dense carbon layer.
10. Application of the sandwich structure MCMB@Si@C silicon-carbon negative electrode material according to claim 9 in lithium-ion batteries.
Citation Information
Patent Citations
Silicon carbon anode material based on mesophase carbon microspheres and preparation method thereof
CN109659514A
High-tap-density double-carbon-layer silicon-carbon composite material and preparation method thereof
CN113193183A
Silicon-carbon negative electrode material for lithium ion battery and preparation method of silicon-carbon negative electrode material
CN117525357A
Silicon / mesophase carbon microsphere composite for lithium ion batteries and preparation method thereof
CN109360945A
Preparation method and application of mesophase carbon micro beads / nanometer silicon composite beads
CN109841826A
Cited By
Silicon-carbon negative electrode material based on conductive carbon skeleton and preparation method of silicon-carbon negative electrode material
CN120637470A